Hadith #4821 - Sunan Abi Dawud - al-Musayb bin Rafa'i al-Asadi المسيب بن رافع الأسدي الكاهلي أبو العلاء; Jabir bin Samra; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Tmym bin Trfh تميم بن طرفة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
AbulQasim (ﷺ) said: When one of you is in the sun (Shams)–Makhlad’s version has “fay'”–and the shadow withdraws from him so that he is partly in sun and partly in shade, he should get up.
Grade: Sahih